231k views
5 votes
Given f(x) = 5/(x-3), simplify f(x+h)-f(x)/h, h does not equal 0 when x = -6

Given f(x) = 5/(x-3), simplify f(x+h)-f(x)/h, h does not equal 0 when x = -6-example-1

1 Answer

6 votes

Answer:

a)
(f(x+h)-f(x))/(h)=(-5)/((x+h-3)(x-3))

b)
(f(h-6)-f(-6))/(h)=(5)/(9h-81)

Explanation:

The given function is
f(x)=(5)/(x-3)


f(x+h)=(5)/(x+h-3)


(f(x+h)-f(x))/(h)=((5)/(x+h-3)-(5)/(x-3))/(h)


(f(x+h)-f(x))/(h)=(5(x-3)-5(x+h-3))/(h(x+h-3)(x-3))


(f(x+h)-f(x))/(h)=(5x-15-5x-5h+15)/(h(x+h-3)(x-3))


(f(x+h)-f(x))/(h)=(-5h)/(h(x+h-3)(x-3))


(f(x+h)-f(x))/(h)=(-5)/((x+h-3)(x-3))

When x=-6


(f(h-6)-f(-6))/(h)=(-5)/((-6+h-3)(-6-3))


(f(h-6)-f(-6))/(h)=(-5)/((h-9)(-9))


(f(h-6)-f(-6))/(h)=(5)/(9h-81)

User Arshin
by
6.3k points